(untitled) (International Journal of Engineering and Computer Science, 2018)
the primary reason for the paper is to build up a model of Black Box For vehicle finding that can be introduced into any vehicle to track its operations. This model can be planned with least number of sensors and circuits with minimal effort so that everybody can bear. This can add to build more secure vehicles, enhancing the treatment for accident casualties, helping insurance agencies with their vehicle crash examinations, and improving street status keeping in mind the end goal to diminish the death rate due to accidents, tracking the exact location of the car. The ignition secret key framework introduced operating at a profit box will anticipate taking and thefts of autos. Data from these black box can be gathered after an accident and broke down to figure out what the vehicles were doing some time recently, amid and after the accident or occasion